Evaluating the PNI, RAI, SIP and SPI Indices in Mapping Drought Intensity of Iran: Comparing the Interpolation Method and Digital Elevation Model (DEM) - Mahmoud Khosravi; Alireza Movaqqari; Mohammad Reza Mansouri Daneshvar (جغرافیا و پایداری محیط)
Drought is a climatic phenomenon which is resulted by the lack of periodical rainfall. to assess the drought the precipitation data in long-term period for each station are analyzed. In the present study, the rainfall data of 48 synoptic stations in Iran at a 30-year time period (2005-1976) based on the drought occurrences severity was extracted in order to map the drought and evaluate the different regions status in this regards. Then using PNI, RAI, SIP and SPI as the indicaters, the severity of the drought in 2001 was determined to give the optimized model. In 2001 a widespread drought occurred in Iran. So these indices are mapped through the two analysis methods containing spatial interpolating and digital elevation models. Finally, the adaption of the zonation maps revealed that the RAI and PNI indices have the more susceptibility and show the spatial distribution of drought intensity. Therefore by comparing drought intensity zoning maps and according to drought dependence on weather systems, it could be concluded that interpolation analysis without using the digital elevation model is the best method for evaluation of drought severity.